Intraoperative maternal complications of the caesarean section: a cross-sectional study at the Provincial general hospital of Kananga in Democratic Republic of Congo - Kayembe, Antoine Tshimbundu; Biakutuele Beya, Trésor; Molere Mikando, Clovis (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The maternal complications of caesarean section make it considered a riskier route of delivery than the vaginal route. The caesarean patient in fact combines the risks of giving birth and those of abdominal surgery. The intraoperative complications can compromise the vital prognosis and the obstetrical and functional future of the parturient. The aim of our study was to determine the epidemiological, clinical and therapeutic profile of intraoperative maternal complications of cesarean section at the Provincial General Hospital of Kananga from January 1, 2014 to December 31, 2020. Methods: This cross-sectional study is performed on a series of cases from the medical files of caesarean patients who suffered from intraoperative complications of caesarean section and based on non-probabilistic sampling of suitability for case selection. Our sample is constituted of 361 cases of intraoperative complications of caesarean section. Results: The frequency of intraoperative complications of caesareans is of 25.87% with an annual average of 51.60 (SD 5.62) cases per year, the average age of patients is 27.39 years, primiparous are the most affected with 27.44%, preoperative haemorrhages are the intraoperative complications most encountered in 74.94%, surgical repair is the most established treatment in 56.00% of cases, the maternal death rate due to intraoperative complications of caesareans is 0.32% of live births. Conclusions: Intraoperative complications of caesarean section constitute a public health problem. Our results can serve as a basis for in-depth studies on the intraoperative complications of caesarean section in order to lower the risks associated with its practice in our environment.